2022
DOI: 10.3390/ijerph19159518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intensity and Duration of Exercise on Gut Microbiota in Humans: A Systematic Review

Abstract: (1) Background: The gut microbiota might play a part in affecting athletic performance and is of considerable importance to athletes. The aim of this study was to search the recent knowledge of the protagonist played by high-intensity and high-duration aerobic exercise on gut microbiota composition in athletes and how these effects could provide disadvantages in sports performance. (2) Methods: This systematic review follows the PRISMA guidelines. An exhaustive bibliographic search in Web of Science, PubMed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 80 publications
0
34
1
Order By: Relevance
“…Exercise and physical activity have also been shown to change the composition of the gut microbiota, something which is associated with improved energy homeostasis and regulation (for a comprehensive revision, please refer to [ 42 , 104 ]) [ 42 , 104 , 105 , 106 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%
“…Exercise and physical activity have also been shown to change the composition of the gut microbiota, something which is associated with improved energy homeostasis and regulation (for a comprehensive revision, please refer to [ 42 , 104 ]) [ 42 , 104 , 105 , 106 ].…”
Section: Gut Microbiota In Children and Adolescents With Asdmentioning
confidence: 99%
“…Cumulative data indicate that gut bacteria are sensitive to modulation by physical activity, as demonstrated by studies using models of training and hypoactivity. Sports performance studies have also shown interesting and promising results [3].…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, the microbiota of the healthy gastrointestinal system has about 800 species of bacteria. Thousands of these microorganisms live in symbiosis with fungi, archaea, and viruses that characterize every human being with maximum concentration in the colon [2,3]. Thus, the human microbiome has about 3 million genes in the gastrointestinal tract, which corresponds to 150 times more than the human genome [1].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations